EFEKTIFITAS SITUS BERBASIS KECERDASAN BUATAN DALAM MENDESAIN TES KETERAMPILAN MENDENGAR TOAFL - Muh Sabilar Rosyad; Muhammad A'inul Haq (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2022)
Abstract: This study aims to determine the advantages of the site and how to use it to produce TOAFL audio text understanding audio, as well as some of the obstacles and solutions to its utilization. This study uses a qualitative approach with descriptive type, using triangulation method in processing and analyzing the results, and data collected through documentation and interviews. The results of the study show that: (1) the site pampers its users with several voice options based on gender and nationality, of which 14 Arabic native voices are currently available; (2) there are features that make it easy for site users to get the desired recordings through speed, volume settings, formats, effects, tones, sizes, and sample rides; (3) the site can be accessed for free with a maximum limit of 400 words per recording and 30 languages with 70 different natives, as well as cloud storage is available; 4) the steps for using the site start with logging in go to the url address, login with email, type the text to be recorded on the white board provided, select the driving engine, language and native, give a touch according to your taste through the settings feature provided. available, press the record button then download the results; 5) The obstacles that are often found are the pronunciation of harakat, the pronunciation of nakirah and ma’rifah, and the pronunciation of two words into one word. all of this can be overcome by placing the harakat according to the i'rab rules and above the alif lam qamariyah (makrifah) and placing the second word on a new line below it.Keywords: Listening Skill, VoiceMaker, Artificial Intelligence